2019
DOI: 10.1038/s41598-019-48195-0
|View full text |Cite
|
Sign up to set email alerts
|

Multigene phylogeny of root-knot nematodes and molecular characterization of Meloidogyne nataliei Golden, Rose & Bird, 1981 (Nematoda: Tylenchida)

Abstract: The root-knot nematodes of the genus Meloidogyne are highly adapted, obligate plant parasites, consisting of nearly one hundred valid species, and are considered the most economically important group of plant-parasitic nematodes. Six Meloidogyne species: M . arenaria , M . hapla , M . incognita , M . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 46 publications
2
28
1
Order By: Relevance
“…These results lead us to conclude that these three MIG genomes descend from a single, common hybridization event. Curiously, the maximum likelihood topology inferred with POInT for these three organisms differs from both of the published ones (Tigano et al 2005;Brito et al 2015;Szitenberg et al 2017;Álvarez-Ortega et al 2019): we speculate that it may be difficult to infer phylogenetic relationships among these species with standard gene tree approaches due to the paralogy introduced by the triploidy.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…These results lead us to conclude that these three MIG genomes descend from a single, common hybridization event. Curiously, the maximum likelihood topology inferred with POInT for these three organisms differs from both of the published ones (Tigano et al 2005;Brito et al 2015;Szitenberg et al 2017;Álvarez-Ortega et al 2019): we speculate that it may be difficult to infer phylogenetic relationships among these species with standard gene tree approaches due to the paralogy introduced by the triploidy.…”
Section: Resultsmentioning
confidence: 55%
“…These nematodes' adaptability is illustrated by their rapid invasions of numerous crop species in the few thousand years since the origins of agriculture (Lunt et al 2014). As suggested by the cartoon phylogeny in Figure 1A, the relationships of these three MIG species are still contested, with some published studies proposing that M. arenaria and M. javanica are sister to each other (Tigano et al 2005;Szitenberg et al 2017) and others arguing for M. incognita and M. arenaria as sisters (Brito et al 2015;Álvarez-Ortega et al 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate and rapid identification of nematodes is essential for their control. It has been shown that sequences of nuclear ribosomal genes: 18S rRNA, ITS rRNA, the D2-D3 of 28S rRNA, IGS rRNA and mitochondrial genes: COII-16S rRNA fragment, COI and COII clearly differentiate M. hapla from all other root-knot nematodes [3]. Several specific primers have been designed for the diagnostics of this species using conventional PCR [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular characterization followed the methods described in Álvarez-Ortega et al (2019) . The ribosomal ITS and LSU sequences were analyzed and aligned using the program BioEdit ( Hall, 1999 ), aligned using CLUSTAL W ( Thompson et al, 1994 ).…”
mentioning
confidence: 99%